Model Pembelajaran Tahfidz di SMAN 2 Pare (Studi Kasus di SMAN 2 Pare) - Kunaenih Kunaenih; Firdaus Firdaus; Nadiah Nadiah; Nurhayati Nurhayati; Putri Eka Sari; Dia Merlinda; Nabilah Hasyim (Universitas Indraprasta PGRI Jakarta, 2023)
This study aims to describe how the application of the tahfidz learning model at SMAN 2 Pare. This research is qualitative research using analytical descriptive method. The result of this study indicates that SMAN 2 Pare has implemented the tahfidz al-Qur'an program as a form of implementation of extracurricular activities at the school. Based on the results of research in the field, researchers obtained findings including what activities are contained in the tahfidz program at the school, tahfidz learning materials, tahfidz learning methods, and evaluation. Then some tahfidz students who get achievements, both from inside and outside the school. The success in implementing tahfidz Al-Qur'an program at SMAN 2 Pare is the school's vision and mission factor, the tutor factor who really embraces and guides students, and the Tahfidz House. Factors that influence the implementation of the tahfidz program are internal and external motivations. Among them are from tutors who guide students and also parents.